FORCE STUDY OF REACTIVE LOADS IN KINEMATIC COUPLES OF A WORKING CAPACITY TURNING MACHINE WITH COMPLEX SPACE MOVEMENT AND VARIABLE VOLUME - ZALYUBOVSKYI, MARK; BLAZHENKO, MARIIA; PANASYUK, IGOR (Herald of Khmelnytskyi National University. Technical sciences, 2023)
High productivity when performing finishing technological operations, as well as technological processes of mixing loose fine-dispersed substances, can be achieved with the use of equipment in which working containers perform complex spatial movement. To date, various types of developed felting machines with complex spatial movement of working containers are known. Each type of such equipment corresponds to the implementation of various felting technological operations - separation of parts from sprues, grinding or polishing of products, cleaning of metal parts from corrosion or mixing of loose fine-dispersed substances. During the operation of the rolling equipment, various reactive loads arise in the kinematic pairs, which depend on the design features of the machines. With the use of the automated design system "SolidWorks", 3D modeling and further strength research of a model of a rolling machine with a working capacity with complex spatial movement and variable volume was performed. In the kinematic chain of the machine under study, an additional moving connecting rod link with rotational and translational kinematic pairs is used. During the performance of the force study, the reactions in all rotational and translational kinematic pairs were determined, the influence of the change in the interaxial distance of the working capacity and the additional moving link of the connecting rod on the maximum values of the reactions in the kinematic pairs of the machine was investigated. The presented results of analytical studies can be applied in the relevant design bureaus of machine-building enterprises at the stage of designing equipment with complex spatial movement of working capacities and felting technological processes.
Keywords: reactions; spatial mechanism; connecting rod; working capacity